The effect of glucocorticoids on adipocyte corticotropin receptors and adipocyte responses - Behrens, Catherine M.; Ramachandran, J. (Biochimica et biophysica acta, 1981)
A specific and sensitive assay for determining the binding of adrenocorticotropin (ACTH) to isolated rat adipocytes has been developed and utilized to study the effect of glucocorticoids on ACTH receptor. Measurement of the binding of tritiated ACTH (spec. act. 90 Ci/mmol) to adipocytes isolated from normal, adrenalectomized, and adrenalectomized dexamethasone-treated rats indicated that there are no differences among these three populations in either the magnitude or the affinity of the binding reaction. The binding interaction was found to be of high affinity ( K d = 5.23 + 1.92 · 10 −9 M) and paralleled closely the stimulation of lipolysis ( K m = 2.09 ± 0.35 · 10 −9 M). About 16 300 receptors were calculated to be present per adipocyte. Hormone-induced cyclic 3′,5′-adenosine monophosphate production remained intact after adrenalectomy, thereby confirming that receptors are not lost during steroid deprivation. The lipolytic response did, however, become less sensitive to both ACTH and epinephrine following adrenalectomy. Pre-treatment of adrenalectomized rats with dexamethasone resulted in an increase in basal and hormone-stimulated levels of cyclic AMP and glycerol production to super-normal values. In adipocyte ghost preparations, ACTH and epinephrine sensitive adenylate cyclase activity was not decreased by adrenalectomy and dexamethasone administration did not result in a selective enhancement of ACTH sensitive adenylate cyclase activity. Our results indicate that glucocorticoids do not cause their permissive effects by specific regulation of the ACTH receptor on the adipocyte.